Neurological adverse events of mitotane in adrenocortical carcinoma: results of a pilot study - Mormando, Marilda; Galiè, Edvina; Bianchini, Marta; Lauretta, Rosa; Puliani, Giulia; Tanzilli, Antonio; Anceschi, Umberto; Simone, Giuseppe; Petreri, Gianluca; Graziano, Giuliana; Pace, Andrea; Appetecchia, Marialuisa (Frontiers in Oncology, 2023)
Introduction. Mitotane, the only drug approved by FDA for the treatment of adrenocortical carcinoma, is associated with several side effects including neurotoxicity. The aim of our study is to investigate the relationship between mitotane plasma levels and neurological toxicity.Methods. We have considered 5 patients affected by adrenocortical carcinoma treated with mitotane. The neurological assessment included neurological examination, electroencephalogram, event related potentials (P300) and neuropsychological assessment. All the patients were first considered at the onset of symptoms of neurotoxicity or when mitotanemia levels were above 18 mg/L, for the second time at mitotanemia normalization and subsequently at its further increase or, in case of persistent neurological abnormalities, some months after normalization.Results. At the first neurotoxicity, four patients showed impaired neurological examination, electroencephalogram and P300, three patients impaired neuropsychological assessment, one patient only P300. At mitotanemia normalization, the neurological examination became normal in all patients and electroencephalogram normalized in one patient, improved in another one, continuing to be altered in the other three. P300 latency and neuropsychological assessment normalized in two patients and persisted alterated in the patient experiencing long-term mitotane toxicity. At the third evaluation, in the patient with prolonged mitotane toxicity, the normal mitotanemia in the previous 9 months restored P300 and improved electroencephalogram but not the neuropsychological assessment. In the two patients experiencing a further rise of mitotanemia, neurological examination was normal but P300 and electroencephalogram were alterated.The results of our study highlighted the presence of neurophysiological and neuropsychological abnormalities associated with mitotane values above 18 mg/L.